If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6x + 6 = 0 Reorder the terms: 6 + 3x + 6x = 0 Combine like terms: 3x + 6x = 9x 6 + 9x = 0 Solving 6 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 9x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = 0 + -6 9x = 0 + -6 Combine like terms: 0 + -6 = -6 9x = -6 Divide each side by '9'. x = -0.6666666667 Simplifying x = -0.6666666667
| 11c-13c+5c-(-12)=-3 | | 3y-2-3y=8 | | 12x+10+4x-9= | | 100+100+80=d | | 8m-25=-31+7m | | 0=-4.9t^2+100 | | 8z-16=-22+9z | | -2=3p+7 | | 4x^2+4x-3y+42=0 | | xy-3y-x-9=0 | | 6x-11=10+6x | | f-7=10 | | 13-6f=30 | | m^2-65m=0 | | -48-12+x=-28 | | -6f=30 | | 10(z+4)-2(z-2)=3(z-3)+4(z-2) | | 3cosx+9=7 | | 3r^2+r-16=2r^2-8+8r | | 20.6+2.1x=8.2x | | (X-3i)(x+3i)=y | | 3B-2=5K-3 | | 7(4-2s)-6s=3 | | 56x^2-9x-81= | | L=5w-3 | | 9(a+5.8)+8.2a=5 | | 45a+172= | | 541x=64 | | 64x-541=-803 | | -x^2-9x+3=0 | | 180=13x-8+3x+7x+4 | | 9a^2+12a+7=0 |